Rejection of yaw disturbance in a two-wheeled wheelchair system - Ahmad, Salmiah; Tokhi, M. Osman; Hussain, Zakaria (2009)
In this paper, a virtual wheelchair (WC) model is developed within Visual Nastran (VN) software environment where the model is further linked with Matlab/Simulink for control purposes. The goal is to have stable two-wheeled WC by transforming the two front wheels (caster) to the upright position. Theoretically, when the two big wheels are fed by the same torque, the WC system will only move in one (x-) direction (with a small forward and backward movement before settlement is achieved). On the other hand, WC in VN produces action-reaction forces in terms of friction between the wheels and the defined ground that lead to small degree of rotation with respect to vertical z- axis, (yaw disturbance). Fuzzy logic control is designed in order to eliminate this unwanted rotation of the wheels during lifting and stabilizing phase. Results show that the unwanted rotation of the wheels is successfully reduced.